2013
DOI: 10.1002/ece3.913
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reproductive condition, roost microclimate, and weather patterns on summer torpor use by a vespertilionid bat

Abstract: A growing number of mammal species are recognized as heterothermic, capable of maintaining a high-core body temperature or entering a state of metabolic suppression known as torpor. Small mammals can achieve large energetic savings when torpid, but they are also subject to ecological costs. Studying torpor use in an ecological and physiological context can help elucidate relative costs and benefits of torpor to different groups within a population. We measured skin temperatures of 46 adult Rafinesque's big-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 37 publications
4
38
1
Order By: Relevance
“…We elected to not categorize each T sk reading as normothermic or torpid due to difficulties in accurately recognizing torpor using temperature data (Boyles et al 2011, Brigham et al 2011, Johnson and Lacki 2014. Each transmitter was calibrated by the manufacturer, allowing us to create unique polynomial equations from which we could convert pulse rates into T sk measures.…”
Section: Temperature-sensitive Radio-telemetrymentioning
confidence: 99%
See 1 more Smart Citation
“…We elected to not categorize each T sk reading as normothermic or torpid due to difficulties in accurately recognizing torpor using temperature data (Boyles et al 2011, Brigham et al 2011, Johnson and Lacki 2014. Each transmitter was calibrated by the manufacturer, allowing us to create unique polynomial equations from which we could convert pulse rates into T sk measures.…”
Section: Temperature-sensitive Radio-telemetrymentioning
confidence: 99%
“…Studies examining the use and thermal benefits of buildings in areas with alternative roosts are uncommon but are needed to evaluate the conservation value of buildings for bat populations (Lausen and Barclay 2006, Law and Chidel 2007, Johnson and Lacki 2014. Bats are frequently evicted from buildings, but the removal of these bats, especially maternity colonies, is a conservation concern as WNS continues to cause mortalities in cave-hibernating bat populations across the continent.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal differences in roost selection observed between pregnant and lactating and non‐reproductive females indicated these groups of bats roosted under differing habitat conditions. Many studies have demonstrated differences among reproductive condition classes in thermoregulatory strategies within bat species, especially for non‐reproductive females because they are not constrained by the demands of pregnancy and lactation (Hamilton and Barclay , Cryan and Wolfe , Rambaldini and Brigham , Johnson and Lacki ). We hypothesize that a comparable pattern may exist for northern long‐eared bats; however, the non‐reproductive females in our study were from spring staging, not the maternity season, and could possibly reflect behavior of pregnant females in early stages of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…By roosting in large‐diameter trees, bats likely encounter a more predictable micro‐environment during the day, potentially facilitating lower body temperatures, reduced metabolic rates, and increased energy savings. Bats in this scenario, however, could also be less likely to use passive rewarming as an energy saving strategy to arouse from torpor (Lausen and Barclay ; Rambaldini and Brigham ; Johnson and Lacki a ,). Pregnant and lactating females demonstrated a preference for roost trees in stands with lower basal areas and live tree densities than randomly selected snags (i.e., stand model).…”
Section: Discussionmentioning
confidence: 99%
“…Rafinesque's big-eared bats have broad, short, rounded wings which allow them to glean insects from vegetation and other surfaces, but also increase their risk of extinction due to higher flight costs and limited abilities to disperse over large distances (Safi and Kerth 2004). In the northern portion of their range, they roost in a variety of roosts including caves, rock shelters, artificial roosts, and tree cavities (Johnson and Lacki 2014) but in Coastal Plain regions, they are closely associated with mature bottomland hardwood forests (Bat Conservation International and Southeastern Bat Diversity Network 2013). These forests experienced significant declines (~80%) during the 18th, 19th, and early 20th centuries due to conversion to agriculture (Wear and Greis 2002).…”
mentioning
confidence: 99%